Design and analysis of a low-voltage electrostatic actuated RF CMOS-MEMS switch - Ma, Li Ya; Nordin, Anis Nurashikin; Soin, Norhayati (2013)
This paper presents the design and analysis of a radio frequency (RF) micro-electromechanical system (MEMS) switch with low actuation voltage using MIMOS 0.35μm complementary metal oxide semiconductor (CMOS) process. The advantage of this RF MEMS switch is very low actuation voltage design which is compatible with other CMOS circuit without employing a separate on-chip voltage source or charge pump unit. Moreover, using CMOS technology to design can highly simplify the fabrication process, reduce the cost and improve the device performance. The RF MEMS switch is a capacitive shunt- connection type device which uses four folded beams to support a big membrane above the signal transmission line. The pull-in voltage, von Mises stress distribution and vertical displacement of the membrane, up-state and down-state capacitances, as well as the switch impedance is calculated and analyzed by finite element modelling (FEM) simulation.